GNAQ mutation in port‐wine macrocheilia. (2nd November 2018) - Ma, G.; Yu, Z.; Liu, F.; Wang, L.; Yu, W.; Zhu, J.; Gu, H.; Liu, Y.; Cai, R.; Lin, X.
Summary: Capillary malformations (CMs), also called port‐wine stains, are a type of birthmark which affect about 3 to 5 out of every 1000 newborn babies. Port‐wine macrocheilia (PWM) are CMs that also cause the lips to enlarge. It is known that port wine stains are caused by a mutation in a protein called GNAQ and this study by researchers in P.R. China aimed to figure out how often this mutation occurs in different tissues of PWM, such as skin, mucosa (e.g. the tissue inside the mouth and nose), gland, and muscle. The authors found that the mutation, called GNAQ(R183Q) mutation, was not present in gland samples, but it was detected in 90%, 95% and 95% of the skin, mucosa and muscle samples, respectively. The study also found a positive correlation between the GNAQ mutation frequency and clinical characteristics, meaning that the mutation was linked to symptoms, especially in mucosa. Thus, the authors hypothesize that GNAQ mutation in mucosa of the lips, with or without underlying port wine stain in the skin, may be used as a predictor for early‐stage PWM. The authors suggest that performing a biopsy of mucosa (testing a small skin sample) if doctors think the patient might have underlying port wine stain, could help detect PWM earlier and allow for earlier treatment. Biopsies are practical, convenient, heal rapidly and don't cause scarring. Abstract : Linked Article: Ma et al. Br J Dermatol 2018; 179 :1109–1114